2006
DOI: 10.1021/la061234k
|View full text |Cite
|
Sign up to set email alerts
|

Resistive-Pulse DNA Detection with a Conical Nanopore Sensor

Abstract: In this paper, we describe resistive-pulse sensing of two large DNAs, a single-stranded phage DNA (7250 bases) and a double-stranded plasmid DNA (6600 base pairs), using a conically shaped nanopore in a track-etched polycarbonate membrane as the sensing element. The conically shaped nanopore had a small-diameter (tip) opening of 40 nm and a large-diameter (base) opening of 1.5 microm. The DNAs were detected using the resistive-pulse, sometimes called stochastic sensing, method. This entails applying a transmem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
196
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(214 citation statements)
references
References 51 publications
16
196
0
Order By: Relevance
“…VI.F how synthetic cylindrical and conical nanopores can be fabricated. These pores have been used to investigate the translocation of DNA in folded and unfolded states Chen, Gu, Brandin, et al, 2004;Fologea, Gershow, Ledden, et al, 2005;Storm, Chen, Zandbergen, et al, 2005͒, the translocation duration of DNA ͑Heng et al, 2004;Mara et al, 2004;Karhanek et al, 2005;Harrell et al, 2006͒, which allows unraveling channel-molecule interactions with single-base-mismatch resolution ͑Iqbal et al, 2007͒, the blocked current amplitude during translocation of proteins ͑Han, Schurmann, , and nanobubbles, which dominate the noise ͑Smeets, Keyser, Wu, et al, 2006͒. Zhao et al ͑2007͒ revealed recently that the voltage threshold for permeation of double-stranded DNA bound to a restriction enzyme depends on the genetic sequence.…”
Section: Synthetic Nanoporesmentioning
confidence: 99%
“…VI.F how synthetic cylindrical and conical nanopores can be fabricated. These pores have been used to investigate the translocation of DNA in folded and unfolded states Chen, Gu, Brandin, et al, 2004;Fologea, Gershow, Ledden, et al, 2005;Storm, Chen, Zandbergen, et al, 2005͒, the translocation duration of DNA ͑Heng et al, 2004;Mara et al, 2004;Karhanek et al, 2005;Harrell et al, 2006͒, which allows unraveling channel-molecule interactions with single-base-mismatch resolution ͑Iqbal et al, 2007͒, the blocked current amplitude during translocation of proteins ͑Han, Schurmann, , and nanobubbles, which dominate the noise ͑Smeets, Keyser, Wu, et al, 2006͒. Zhao et al ͑2007͒ revealed recently that the voltage threshold for permeation of double-stranded DNA bound to a restriction enzyme depends on the genetic sequence.…”
Section: Synthetic Nanoporesmentioning
confidence: 99%
“…Non-correlated events, characterized by fast and shallow dips in the ionic current, could be attributed to DNA molecules bumping against the pore instead of translocating through it 35 . During such bumping events, the clogging of the pore is too weak to effectively change the electrostatic potential in the proximities of the pore and gate the GNR.…”
Section: Dna Detection Through a Nanopore Using Gnrsmentioning
confidence: 99%
“…Track-etched nanopores are fabricated by etching the ion tracks inside organic foils, 1 and they gain more and more attention due to their applications in biosensor, 2,3 DNA sequencing, 4,5 mimicking the ion channel, 6,7 and energy conversion. 8 In all these applications, surface charge is crucially important, since it governs ion transport through the pores, especially when the salt concentration is low.…”
Section: Introductionmentioning
confidence: 99%